PENGARUH USIA, TINGGI BADAN DAN RIWAYAT PEMBERIAN ASI EKSKLUSIF TERHADAP STUNTING PADA BALITA - Sumardiyono Sumardiyono (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: Stunting is a chronic condition that describes stunted growth due to long-term malnutrition. Stunting can be influenced by the lack of nutrition, low birth weight exclusive breastfeeding, duration of exclusive breastfeeding. Objective: to analyze the effect of age, height, and history of exclusive breastfeeding on stunting using multiple logistic regression tests and the presentation of the regression equation model followed by the probability of stunting in toddlers. Methods: The study population was toddlers who had medical record data at the public health center "X" in Banyuanyar Surakarta in October 2019. By using a consecutive sampling technique, a sample of 30 children was obtained. Results: age, height, and history of exclusive breastfeeding together affected stunting (F = 25,676, p = 0,000), with a joint effect of 71.9%. Age, height, and history of exclusive breastfeeding individually also affected stunting, respectively age (t = 3,656, p = 0.001), height (t = -4,499, p = 0,000), and history of breastfeeding exclusive (t = 3.207, p = 0.004). Conclusion: exclusive breastfeeding for toddlers can improve nutritional status, thereby reducing the chances of toddlers experiencing stunting.